The Transformative Role Of Droplet Digital PCR In The Clinical Laboratory: Principles, Applications, And Implementation Considerations For Diagnostics (The Review of Diabetic Studies, 2024)
Droplet digital Polymerase Chain Reaction (ddPCR) represents a critical evolutionary leap in nucleic acid quantification, moving beyond the inherent limitations of relative measurement methods toward delivering high-precision, absolute target measurement (1). This review outlines the technological foundation, analytical advantages, and crucial clinical applications of ddPCR, specifically addressing the practical implementation challenges relevant to laboratory specialists and technicians. The core methodology of ddPCR involves partitioning the sample into thousands of discrete, nanoliter-sized reaction chambers—microdroplets—and then quantifying the number of positive reactions based on the Poisson distribution (2). Key analytical characteristics of ddPCR include notably high sensitivity for targets present in low abundance, robust specificity, exceptional reproducibility, and a good tolerance to PCR inhibitors when compared with conventional molecular methods (3, 4). These characteristics render ddPCR a valuable tool across diverse clinical fields. In infectious disease diagnostics, ddPCR enables accelerated turnaround time (TAT) for highly consequential conditions such as bloodstream infections and permits precise monitoring of low-level viral reservoirs (5). In oncology, ddPCR provides high-resolution copy number variation (CNV) analysis, which is critical for stratifying clinical outcomes and guiding targeted therapies in cancers, including advanced prostate cancer (6, 7). However, the implementation of ddPCR in clinical laboratories requires careful consideration of the substantial initial investment and the critical necessity for standardized assay validation protocols covering the Limit of Detection (LOD) and Limit of Quantification (LOQ) to ensure reliable and widespread clinical adoption (8, 9).